Reação de crisântemos a Meloidogyne incognita, Meloidogyne javanica e Meloidogyne enterolobii - Gonçalves, Lucivane Aparecida [UNESP]; Brida, Andressa Lima De [UNESP]; Silva, Maria De Fátima Almeida [UNESP]; Bueno Junior, Cezar [UNESP]; Wilcken, Silvia Renata Siciliano [UNESP] (Grupo Paulista de Fitopatologia, 2014)
This study aimed to evaluate the resistance of 14 chrysanthemum varieties to the nematodes Meloidogyne incognita, M. javanica and M. enterolobii. The experiment was conducted in a completely randomized design, consisting of 15 treatments and 4 replicates per nematode species. Each plot was constituted of one plant per pot; plants were kept in a greenhouse and inoculated with 5,000 eggs and possible juveniles of M. incognita, M. javanica and M. enterolobii. After 60 days, the rates of egg masses, the number of nematodes per gram of root and the reproduction factor were evaluated. The varieties showed immunity to M. incognita, M. javanica and M. enterolobii, except 'Capello Vermelho' and 'White Reagon', which were susceptible and resistant, respectively, to M. incognita.

Este trabalho teve como objetivo avaliar a resistência de 14 variedades de crisântemos aos nematoides Meloidogyne incognita, M. javanica e M. enterolobii. O experimento foi conduzido em delineamento inteiramente casualizado, constando de 15 tratamentos e 4 repetições, por espécie de nematoide. Cada parcela foi constituída por uma planta por vaso, mantidas em casa de vegetação e inoculadas com 5.000 ovos e eventuais juvenis de M. incognita, M. javanica e M. enterolobii. Após 60 dias, os índices de massas de ovos, número de nematoides por grama de raiz e o fator de reprodução foram avaliados. As variedades apresentaram imunidade a M. incognita, M. javanica e M. enterolobii, exceto 'Capello Vermelho' e 'White Reagon', que foram respectivamente suscetível e resistente a M. incognita.
Chrysanthemum reaction to Meloidogyne incognita, Meloidogyne javanica and Meloidogyne enterolobii
Keywords: Ornamental; Crisântemo; Nematoide das galhas; Ornamental; Chrysanthemum; root-knot nematodes